PENGARUH SENAM TERHADAP PENURUNAN DEPRESI PADA LANSIA DI POSYANDU KEL. MADYOPURO, KEC. KEUNGKANDANG MALANG - Nur Iffah (Prosiding Conference on Research and Community Services, 2019)
The aging process is a natural process in human in which changes occur and biological, psychological, and social functions decline. Mental health disorders begin to be experienced by the elderly when they experience the signs of the agin process such as feeling of sadness, anxiety, loneliness an depression. The most common mental health problem that arices in the elderly is depression. Low impact aerobic exercises can be used to improve one’s mood and to remedy various psychiatric symptoms and also can reduce anxiety, depression, fatigue and confusion. This study aims to determine the effectiveness of exercise on the decrease of depression level in the elderly. This Quasi-experimental research specifically used Non-Randomized Control Group Pre Test-Post Test Design which was conducted in health care center for elderly in RW 5 AndRW 12 MadyopuroKedungkandangMalang. Samples that met the criteria were 26 respondents which then were divided into two groups based on the place. Thirteen elderly respondents were taken from health care center for elderly in RW 12 were treated with exercises that were done (three temes) a week for four weeks. Thirteen other respondents from health care center for elderly in RW 5 were used as the control group. Both groups performed pretest and post-test at the same time to determine the level of depression using the Geriatric Depression Scale (GDS). The results showed that there was influence of exercise to social interaction in elderly individuals (p =0.042), there was influence of exercise to depression in elderly individuals (p= 0.011),  there was no correlation between social interaction and depression in elderly individuals (p= 0.484). The conclusion of the study is that elderly exercises can reduce depression in eld erly individuals. Exercises are recommended in order to give positive effects in reducing the depression in elderly.